Biomechanical details regarding the efficiency of start in sprinting events - Petrescu, T.-D.; Ionescu Bondoc, D. (Annals of the University Dunarea de Jos Galati, Fascicle XV: Physical Education and Sport Management, 2019)
Our research is based on a study on the efficiency of athletic start in sprinting events, based on biomechanical analyses of the "key" moments from the start of a sprinter, component of the national athletic team. The study wishes to highlight a number of important details that, under the most favorable conditions, would allow the athlete a better use of the available potential at the start. The research was based on high-frequency footage recordings of a top runner who ranked third at the National Athletics Indoor Championships.After analyzing and interpreting the main sequence of the phases of each step after running out of the starting blocks, some technical aspects have been highlighted, which have proved to be restrictive on the performance of the athlete in the competition.These minor technical errors highlighted in our research may be considered to have made the difference between our subject and the winner of the competition.We believe that by remedying these small technical deficiencies, through specific analytical exercises, the value of performance of our subject can be substantially improved.The paper is an analysis of the moments of completion of pulses on the first steps of detachment from the starting block and the moments in which the contact is made with the runway after each phase of flight.For each of these moments, the impulse angles of the first steps and their growth rate were analyzed, the ground contact angles at landing after each flight phase.